2018
DOI: 10.2147/jpr.s174475
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic pain modulation after spinal cord injury by breathing-controlled electrical stimulation (BreEStim) is associated with restoration of autonomic dysfunction

Abstract: BackgroundRecent findings have implicated supraspinal origins from the pain neuromatrix– central autonomic network (PNM–CAN) in the generation of neuropathic pain (NP) after spinal cord injury (SCI). The aim of this study was to further investigate the theorized PNM–CAN mechanisms in persons with SCI by using a centrally directed pain intervention, provided by breathing-controlled electrical stimulation (BreEStim), to measure resultant autonomic changes measured by time and frequency domain heart rate variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…However, we do not agree with the authors that BreEStim produces analgesic effects only for the arm. Our recent series of experiments has provided evidence that BreEStim has central analgesic effects in painfree healthy subjects (7-9) and in subjects with SCI (10,11). This study provided further evidence for this central analgesic effect.…”
Section: Commentary On: "Combined Transcranial Direct Current Stimulasupporting
confidence: 61%
“…However, we do not agree with the authors that BreEStim produces analgesic effects only for the arm. Our recent series of experiments has provided evidence that BreEStim has central analgesic effects in painfree healthy subjects (7-9) and in subjects with SCI (10,11). This study provided further evidence for this central analgesic effect.…”
Section: Commentary On: "Combined Transcranial Direct Current Stimulasupporting
confidence: 61%
“…The successful activation of the pain neuromatrix–central autonomic network can be quantified by looking at combined effects on autonomics as measured by heart rate variability [ 67 ]. A small sample of patients post SCI completed a controlled trial in which the treatment group received 120 BreEStim impulses [ 67 ]. The treatment group experienced a decrease in heart rate variability, indicating that BreEStim may provide for a viable treatment strategy for decreasing post-SCI pain [ 67 ].…”
Section: Clinical Evidencementioning
confidence: 99%
“…A small sample of patients post SCI completed a controlled trial in which the treatment group received 120 BreEStim impulses [ 67 ]. The treatment group experienced a decrease in heart rate variability, indicating that BreEStim may provide for a viable treatment strategy for decreasing post-SCI pain [ 67 ].…”
Section: Clinical Evidencementioning
confidence: 99%
“…Despite its high prevalence, managing persons with SCI and NP is often clinically challenging, owing largely in part to our limited understanding of its precise pathophysiology (2,3). A score of recent, innovative studies have presented increasing evidence for pathologic neuromodulation at the supraspinal level as being responsible for post-SCI NP (4)(5)(6)(7). The neural structures implicated in this pathogenesis include the insula, anterior cingulate cortex (ACC), and the prefrontal cortex, which collectively comprise part of the pain neuromatrix (PNM) (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, elegantly designed studies utilizing functional MRI found these cortical areas within the PNM to demonstrate increased activity specifically in persons with SCI + NP relative to able bodied persons (AB) upon pain induction (4). These neural structures also were found to be highly interconnected in proximity and function to the central autonomic network (CAN) in persons with SCI relative to AB persons (4,5,(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%